Work practices as to handling of mercury among senior clinicians at the U.P. College of Dentistry - Crisostomo, Aurea B.
A survey was conducted among senior clinicians at the U.P. College of Dentistry regarding work practices as to handling of mercury on the basis of prevalence and safety. Results of the survey revealed that the most prevalent work practice is the use of squeeze cloth in avoiding contact with an amalgam mix. Moreover, the study showed that there are more clinicians whose unsafe work practices are greater than safe work practices.